Dampak Organisasi terhadap Keterampilan Public Speaking Mahasiswa Universitas Muhammadiyah Jember (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This study aims to examine the effect of students’ organizational involvement on public speaking skills among students of Universitas Muhammadiyah Jember. Public speaking skills are essential soft skills required by students in both academic and professional settings, particularly for those who actively engage in public and organizational activities. This research employed a quantitative approach with an associative research design. The independent variable in this study was students’ organizational activeness (X), while the dependent variable was public speaking skills (Y). The research sample consisted of 169 students of Universitas Muhammadiyah Jember selected using proportionate stratified random sampling. Data were collected through a closed-ended questionnaire using a Likert scale, which had been tested for validity and reliability. Data analysis was conducted using descriptive and inferential statistical methods. The results showed that the organizational activeness instrument had a high level of reliability, while the public speaking skills instrument demonstrated a moderate level of reliability. Overall, students’ involvement in organizations plays an important role in developing public speaking skills through communication experiences, active participation, and increased self-confidence. This study is expected to serve as a reference for higher education institutions and student organizations in designing programs that support the development of students’ soft skills, particularly public speaking abilities.